Building custom tasks for SQL Server Integration Services taking a low-cost approach to applying the power of .NET in ETL solutions - Leonard, Andy (Apress, 2017)
Learn to build custom SSIS tasks using Visual Studio Community Edition and Visual Basic. Bring all the power of Microsoft .NET to bear on your data integration and ETL processes, and for no added cost over what you've already spent on licensing SQL Server. If you already have a license for SQL Server, then you do not need to spend more money to extend SSIS with custom tasks and components. Why are custom components necessary? Because even though the SSIS catalog of built-in tasks and components is a marvel of engineering, there do remain gaps in the functionality that is provided. These gaps are especially relevant to enterprises practicing Data Integration Lifecycle Management (DILMS) and/or DevOps. One of the gaps is a limitation of the SSIS Execute Package task. Developers using the stock version of that task are unable to select SSIS packages from other projects. Yet it's useful to be able to select and execute tasks across projects, and the example used throughout this book will help you to create an Execute Catalog Package task that does in fact allow you to execute a task from another project. Building on the example's pattern, you can create any task that you like, custom tailored to your specific, data integration and ETL needs. What You Will Learn: Configure and execute Visual Studio in the way that best supports SSIS task development Create a class library as the basis for an SSIS task, and reference the needed SSIS assemblies Properly sign assemblies that you create in order to invoke them from your task Implement source code control via Visual Studio Team Services, or your own favorite tool set Code not only your tasks themselves, but also the associated task editors Troubleshoot and then execute your custom tasks as part of your own project iv>.
Includes bibliographical references. - Online resource; title from PDF title page (EBSCO, viewed July 12, 2017)
Keywords: SQL server; Database management; Database design; Client/server computing; Bases de données; Gestion; Bases de données; Conception; Architecture client-serveur (Informatique); Databases; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference